Impact of COVID-19 in AChR Myasthenia Gravis and the Safety of Vaccines: Data from an Italian Cohort - Antonino Lupica; Vincenzo Di Stefano; Salvatore Iacono; Antonia Pignolo; Martina Quartana; Andrea Gagliardo; Brigida Fierro; Filippo Brighina (MDPI AG, 2022)
Background and aims. Patients with Myasthenia gravis (MG) are considered vulnerable as they may present with respiratory muscle weakness and because they are on immunosuppressive treatment; thereby, COVID-19 may have a detrimental effect on these patients. Vaccines against COVID-19 are currently available and it has been shown as they can prevent severe COVID-19 in vulnerable patients. Notwithstanding their efficacy, vaccine hesitancy has not been completely dispelled in the general population. Unfortunately, there is limited data about the safety of these vaccines in MG patients. The aims of this study are to evaluate the impact of COVID-19 in a MG cohort, the adherence to COVID-19 vaccination in Italy and vaccine safety in MG patients. Methods. A retrospective cohort study of MG patients attending the Neuromuscular Clinic of the University Hospital "Paolo Giaccone" of Palermo, Italy, was performed. Patients underwent telephone interviews with a dedicated questionnaire on SARS-CoV-2 vaccination and infection. Vaccine safety was assessed though the evaluation of vaccine-related adverse events (AEs) and comparisons of MG-ADL scores before and after vaccination. Patient worsening was defined as two or more point increases in MG-ADL scores. Results. From a total of 90 participants, 75 answered the questionnaire and 70.5% of them (n = 53) received the vaccine; ten patients did not receive vaccination and 3 patients were partially vaccinated. Among the vaccinated patients, about 45% (n = 24) experienced at least one AE, with a complete resolution within one week. No serious AEs and life-threatening conditions were observed. Globally, MG-ADL scores did not worsen after vaccination. Nine unvaccinated patients experienced SARS-CoV2 infection and four of them (44%) died-one patient required respiratory support, whereas three patients were asymptomatic. Conclusions. COVID-19 significantly impacted MG patients with an increase in mortality due to respiratory sequelae. Vaccines against SARS-CoV-2 showed good short-term safety in MG patients, who may take advantage of vaccination to avoiding life-threatening complications such as COVID-19 pneumonia.